EVALUATING TIKTOK AS A DIGITAL ELT RESOURCE: A COMPARATIVE CONTENT ANALYSIS OF INSTRUCTIONAL QUALITY AND PRAGMATIC COMPETENCE BETWEEN LOCAL AND NATIVE SPEAKER CREATORS - Aisyah Vikha Aryadi; Sujito (Jurnal Riset Multidisiplin Edukasi, 2026)
Short-form video platforms, particularly TikTok, have emerged as significant informal English language learning environments, yet the instructional quality and pragmatic competence coverage of creator-produced ELT content remain largely unexamined. This study conducts a qualitative comparative content analysis of twenty TikTok videos (ten produced by an Indonesian local creator, @gurukumrd, and ten by a native speaker creator, @englishwithlucy to evaluate and compare their instructional approaches across two analytical dimensions: instructional quality and pragmatic competence coverage. Drawing on Mayer's (2009) cognitive theory of multimedia learning, Searle's (1969) speech act theory, and Brown and Levinson's (1987) politeness theory, the analysis reveals two pedagogically distinct but complementary content profiles. @gurukumrd demonstrates consistent contrastive pragmatic scaffolding, dialogic scenario construction, and explicit orientation toward the L1 interference patterns of Indonesian learners. @englishwithlucy demonstrates high production clarity, lexical depth, and authentic cultural modeling, delivered through a monologic format that prioritizes definitional accuracy over social contextualization. Neither approach is pedagogically superior; rather, the findings suggest that local and native speaker ELT creators offer complementary instructional affordances that, when considered together, more comprehensively address the pragmatic competence needs of Indonesian EFL learners. Implications are discussed for EFL educators, content creators, and researchers in digital language learning.